DEPICTING A PORTRAIT OF A PERSON IN ONE COLOUR ON A SOLID BACKGROUND (GRISAILLE) (European Journal of Interdisciplinary Research and Development, 2025)
This article describes the composition of the portrait and the human figure. The rules of the methodical-step method of drawing a portrait of a human figure in the grille technology. The constructive construction of the portrait, the correct placement of the subject, the analysis of anatomy, and the spatial perspective of oil painting were considered.